Voices of ardent readers: one in concert - Chong, Su Li; Renganathan, Sumathi (MELTA (Malaysian English Language Teaching Association), 2008)
What does it take to be an ardent reader? Research on literacy and reading motivation has shown that one’s upbringing and background, specifically the relationship between attitude and belief are crucial factors in shaping one’s reading habits. With that as its basis, this paper captures significant findings from interview data of university students of differing backgrounds who are proficient in English and more importantly, who share the love of reading. The researchers aim to better understand the reading experience of these Malaysian readers by listening to their accounts of early and current reading experiences. The researchers choose to analyze and understand the data from a qualitative approach because it accords these voices more depth. While each voice is regarded uniquely in its own historical context and construct, their voices when in concert, point to the construction of new insight in the researchers’ stance on what it takes to be an ardent reader. To learn from these voices is to reiterate not how infrequently young Malaysians read, but how possible it is to shape young Malaysians into ardent readers.